Landscapes of the socio-political : Irish women playwrights from 2000 - O'Keeffe Doyle, Rosie Patricia (Trinity College (Dublin, Ireland). Department of Drama, 2017)
This thesis looks at intersections between women, theatre and Irish society since the turn of the millennium. There is a history of internalized misogyny throughout Irish theatre and, in part, the impetus for the study has been to resist the overlooked and unregarded presence of Irish women playwrights over the last sixteen years. Use is made of fifteen contemporary plays by women to illustrate five important social themes; the position of motherhood in Ireland, queer and gender identities, sex and sexuality, violence against - and by - women, and issues surrounding aging processes.
Keywords: Drama, Ph.D.; PhD Trinity College Dublin, 2017